(untitled) (Research, Society and Development, 2022)
This study aims to analyze in the literature the history of the nurse’s performance for the disease Diabetes Mellitus, and to discuss its probable causes. For this, an integrative literature review was carried out, carried out in the SCIELO, VHL and Google Scholar databases. As a result, we found adherence to DM treatment, that there are individuals who have knowledge about the disease and others do not, perhaps due to the lack of effective guidance from professionals and, consequently, complications arise. Further studies are needed, especially in the gap in health education for patients with DM and on its benefits, and that these do not end at the time of consultation, and as for professionals, it is important that there is continued training on the subject, with the with the aim of improving the care offered to this public every day.